Kepemimpinan Kepala Madrasah Dalam Pengembangan Lembaga Pendidikan Islam - Rosid, Mohamad (Universitas KH. A. Wahab Hasbullah, 2023)
Madrasah head leadership is defined as a model or type of madrasa head leadership that is appropriate to the situation in order to influence, direct, guide subordinates by strengthening confidence, support, encouragement and cooperation in order to achieve the goals and objectives of educational institutions. The development of an educational institution depends on the quality of the madrasa head as an educational leader because a very important factor in the educational process is a quality educational institution, so a quality educational institution will automatically be able to produce a quality generation as well. According to its type, this research is descriptive qualitative research with a phenomenological approach. Data collection methods use observation, interviews, documentation, questionnaires. And the data analysis is descriptive qualitative. From the research results, it can be concluded that the leadership qualities of the madrasa head at MTs NU Mojosari include having strong responsibilities such as admitting shortcomings and mistakes in all his activities as a madrasa head, taking part in seminars and training sessions outside the school and having the courage to make decisions. And the efforts are to develop curriculum, human resources, infrastructure and community participation. The supporting factors are supporting infrastructure, teachers together in managing the curriculum and the teaching and learning process. Apart from that, the inhibiting factors are the problems of teachers, funding, students' varying abilities and psychological well-being as well as low level of community participation.